2013
DOI: 10.1039/c3tc30464g
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz and optical properties of nematic mixtures composed of liquid crystal isothiocyanates, fluorides and cyanides

Abstract: Several simple nematic eutectic liquid crystal mixtures composed of different two and three ring isothiocyanato compounds as well as mixtures consisting of analogous cyano and fluoro compounds were formulated. The optical properties of the thereby obtained mixtures, i.e. refractive indices, birefringence and absorption coefficients a e and a o are measured in the frequency range between 0.5 and 2.5 THz and in the visible range at 589 nm. Our results show that two mixtures can be identified, which seems particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 31 publications
1
13
0
1
Order By: Relevance
“…The level of absorption losses of mixtures composed of isothiocyanates, cyanides and fluorides (absorption coefficient α e and α o ) decreases as follows in THz region [133].…”
Section: Mixture Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The level of absorption losses of mixtures composed of isothiocyanates, cyanides and fluorides (absorption coefficient α e and α o ) decreases as follows in THz region [133].…”
Section: Mixture Formulationmentioning
confidence: 99%
“…They exhibit not only reduced absorption losses but also a small dichroism because α e and α o of the component are averaged and levels them out [133].…”
Section: Mixture Formulationmentioning
confidence: 99%
“…It has been reported that three benzene rings connected directly or with bridge group exhibit larger birefringence than structures with fewer rings. [28] As shown in Figure 3, BL037 has a flat refractive index in THz spectrum and the birefringence value increases with frequency from 0.17 at 0.5 THz to 0.21 at 2.5 THz. However, the absorption in the ordinary states increases dramatically with frequency (44.6 cm −1 at 2.5 THz), while the extraordinary absorption slope is much less steep.…”
Section: Data Analysis and Discussionmentioning
confidence: 98%
“…According to Reuter et al [28], LCs with NCS groups enable higher birefringence over a broad temperature range than CN groups and have rather low viscosity. This material has been studied by Trushkevych et al [29], but they did not use very efficient alignment schemes such as high voltage and the THz band they measured is limited to 0.5-1.6 THz.…”
Section: Data Analysis and Discussionmentioning
confidence: 99%
See 1 more Smart Citation